Development and testing safe fall strategies for lower limbs exoskeletons - Zagalo, Daniel Sousa Lapa Cupido (2021)
Loss of mobility is among the most impactful consequences of sustaining a spinal cord injury. Wheelchairs provide a considerable degree of mobility to their users, but are not without their drawbacks, most of which are caused by requiring prolonged periods of time in the sitting position. Recently, the field of lower limb exoskeletons has seen considerable developments, and the use of external power technologies has made it possible for users to walk for longer periods of time. However, current exoskeletons do not ensure balance during standing and walking conditions, which leaves their users vulnerable to situations of instability and falls. The goal of this thesis was to investigate safe fall strategies to reduce the severity of the impact in case of a loss of balance with a lower limb exoskeleton. The backwards fall scenario is examined, and a fall strategy is implemented in a simulation environment, using a combination of center of mass and hip joint angle reference signals. The results verified the model’s ability to execute the proposed strategy by following the reference signals, and the strategy was shown to result in safer falls. Further work should be conducted to test this strategy in real-life human-exoskeleton fall scenarios, and to develop strategies for other fall scenarios.